Residents' Satisfaction Towards the Indoor Environmental Quality of Re-engineered Affordable Housing Scheme in Malaysia - Kamaruzzaman, Syahrul Nizam; Razali, Atikah; Ahmad Zawawi, Emma Marinie; Basir, Siti Arni; Riley, Michael (Faculty of Engineering, Universitas Indonesia, 2018)
Malaysia is currently focusing on providing affordable housing all over the country, as part of the plan to tackle the problem of the rising costs of house ownership due to reasons such as the economic crisis and land limitations. However, a limited number of methodical studies have been conducted on residents' feedback on the indoor environment of affordable housing. Indoor Environmental Quality (IEQ) is an important aspect of occupants' wellbeing, as it affects their health and productivity. Therefore, evaluating residents' feedback on IEQ is an important step in gauging building performance and conditions. In addition, the health and productivity of residents needs to be evaluated in order to identify the effect of IEQ on them. A questionnaire survey was used to achieve the study objectives and to gain access to the respondents' views and feedback. The pilot questionnaire study was conducted at two housing apartments in Kuala Lumpur, Malaysia, and the data collected were evaluated and analyzed using SPSS software. The outcome of this pilot study is significant, as it shows the residents' dissatisfaction level towards IEQ factors such as noise, glare and privacy, and other aspects of IEQ that are important, such as ventilation. Additionally, it has been found that the IEQ of the residents does affect their health and productivity. It is anticipated that the outcome of this study will serve as an indicator of building performance improvements needed to achieve a better indoor environment quality for affordable housing in Malaysia.